EXPRESSION OF ANTONYMIC RELATIONSHIPS IN TONGUE TWISTERS WITH THE CONCEPT PLANT (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article investigates the expression of antonymic relationships in tongue twisters that incorporate the conceptual domain plant. Tongue twisters, though primarily associated with phonetic difficulty, demonstrate complex semantic mechanisms, including antonymy. The study examines how plant-related lexical units enter into oppositional relations and how these relations enhance phonetic tension, semantic contrast, and stylistic expressiveness. The analysis shows that antonymy in plant-based tongue twisters is realized mainly through contextual, gradational, and evaluative oppositions rather than strict lexical antonyms.